Know Your Rights Booklet - Trinity FLAC (Trinity Free Legal Advice Centre, 2019)
This booklet details rights relevant to students in their everyday lives, including: landlord and tenancy issues, consumer rights, equality and discrimination, powers of the Gardaí, the right to protest, and rights on a night out.
Keywords: Legal advice; Housing rights; Consumer rights; Ireland; Equality; Discrimination